1995
DOI: 10.1073/pnas.92.22.10354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an additional gene required for eukaryotic nonsense mRNA turnover.

Abstract: Loss of function of any one of three UPF genes prevents the accelerated decay of nonsense mRNAs in Saccharomyces cerevisiae. We report the identification and DNA sequence of UPF3, which is present in one nonessential copy on chromosome VII. Upf3 contains three putative nuclear localization signal sequences, suggesting that it may be located in a different compartment than the cytoplasmic Upfl protein. Epitope-tagged Upf3 (FLAG-Upf3) does not cofractionate with polyribosomes or 80S ribosomal particles. Double d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 26 publications
0
80
0
Order By: Relevance
“…Hybridization analysis to detect Ty1 mRNA was performed as described previously (Lee and Culbertson 1995;Lee et al 1998), and the signals were quantified using a Typhoon Trio phosphorimager and ImageQuant 1.2 software (GE Healthcare, Piscataway, NJ). To measure steady-state levels of pre-rRNA and rRNA in wild-type and bud22D strains, total RNA was prepared and hybridized as described previously (Martin-Marcos et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Hybridization analysis to detect Ty1 mRNA was performed as described previously (Lee and Culbertson 1995;Lee et al 1998), and the signals were quantified using a Typhoon Trio phosphorimager and ImageQuant 1.2 software (GE Healthcare, Piscataway, NJ). To measure steady-state levels of pre-rRNA and rRNA in wild-type and bud22D strains, total RNA was prepared and hybridized as described previously (Martin-Marcos et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The nonsense-mediated mRNA decay (NMD) pathway is a cellular quality control mechanism that degrades aberrant mRNAs harboring premature termination codons (Losson & Lacroute, 1979;Gozalbo & Hohmann, 1990;Maquat, 1995;Caponigro & Parker, 1996;Jacobson & Peltz, 1996;Ruiz-Echevarria et al+, 1996;Weng et al+, 1997)+ This mRNA surveillance pathway functions in all eukaryotic systems examined and appears to have evolved to recognize premature termination events during the protein synthesis process (Pulak & Anderson, 1993;Weng et al+, 1996aWeng et al+, , 1996bWeng et al+, , 1998Czaplinski et al+, 1998Czaplinski et al+, , 1999+ Several genes required for NMD have been identified in the yeast Saccharomyces cerevisiae+ Mutations in the UPF1, UPF2, UPF3, MOF2/SUI1, MOF5, MOF8, and HRPI genes were shown to selectively stabilize mRNAs containing early nonsense mutations without affecting the decay rates of most wild-type mRNAs (Leeds et al+, 1991(Leeds et al+, , 1992Cui et al+, 1995Cui et al+, , 1999He & Jacobson, 1995;Lee & Culbertson, 1995;Gonzalez et al+, 2000)+ Subsequently, Upf1p, Upf2p, and Upf3p were shown to form a complex (He & Jacobson, 1995;Weng et al+, 1996b;He et al+, 1997)+ In other studies using Caenorhabditis elegans, Smg genes were identified whose products were shown to be involved in NMD and a subset of those are homologous to the yeast UPF genes (Pulak & Anderson, 1993;Cali & Anderson, 1998)+…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts produced from CYC1 and cyc1-512 containing constructs+ A and B show agarose northerns with 10 mg of total mRNA from wild-type strains showing the mRNA species present in four different reporter constructs containing either wild-type CYC1 or mutant cyc1-512 sequences in each lane+ Above each lane is the corresponding construct name+ The presence of a 39 PGK1 terminating sequence is designated as PGKt+ Next to each band is a letter that refers to the mRNA species of the approximate sizes given below+ Lanes are numbered below for each panel that correspond to the mRNA species depicted in the cartoons below+ A: Northerns are probed for the CUP1 mRNA sequences present in all of these constructs+ B: Identical northerns as in A but probed for the 39 PGK tag sequence+ Cartoons below the northerns show the plasmid constructs from which each mRNA was made+ The numbers on the left refer to the northern lanes above in A and B+ The skinny open rectangles represent vector sequences; PGK1 sequences are in large open rectangles; inserted flag and CUP1 sequences are also shown; CYC1 or cyc1-512 sequences are shown as a single gray box; the polyadenylation signal sequences, which are deleted in the cyc1-512 constructs, are shown as a black box; the location of the two probes used are indicated as lines under each construct+ Letters designating the 39 ends of the mRNA species seen in the upper northerns are marked with arrows+ Species A-D match previously reported sizes (Zaret & Sherman, 1984) of mRNA species produced from the CYC1 and cyc1-512 sequences+ Approximate sizes in bases of these mRNA species are as follows: A: 530; B: 1250; C: 1350; D: 1550; E: 3200; F: 3500; G: 4500; H: 2200+ codons (Pulak & Anderson, 1993)+ To test this hypothesis, we examined the effects of trans-acting mutations known to alter the mRNA surveillance pathway to determine if they affect the decay of the 39-extended mRNAs+ Transcripts that contain early nonsense codons are degraded by a deadenylation-independent decapping reaction, which leads to 59-to-39 exonuclease degradation+ The enzymes responsible for these reactions are the Dcp1p decapping enzyme LaGrandeur & Parker, 1998) and the Xrn1p 59-to-39 ribonuclease Hagan et al+, 1995)+ As shown in Figure 3B, the 39-extended transcripts were stabilized in both dcp1⌬ and xrn1⌬ strains+ These observations argued that decay of these aberrant mRNAs proceeded by decapping and then degrading in a 59-to-39 direction+ The DCP1 and XRN1 gene products are also required for the decapping and 59-to-39 degradation of normal mRNAs that occurs following deadenylation (Fig+ 2;Decker & Parker, 1993;Hsu & Stevens, 1993;Beelman et al+, 1996)+ In contrast, the degradation of transcripts with early nonsense codons by the mRNA surveillance pathway is inhibited in strains lacking the UPF1, UPF2, or UPF3 genes without an effect on normal mRNA degradation (Leeds et al+, 1991;Lee & Culbertson, 1995;Cui et al+, 1996;He et al+, 1996)+ Therefore, to determine if the 39-extended mRNAs were specifically being degraded by the mRNA surveillance pathwa...…”
Section: An Extended 39 Utr Is a Transferable Mrna Destabilizing Sequmentioning
confidence: 99%